Prostatic Abscess in a Neonate - Veluchamy, Manikandasamy (Cureus, 2020)
Urinary tract infection (UTI) is the most commonly occurring serious bacterial infection in young infants. Uncircumcised male infants have a higher rate of UTI when compared with circumcised male infants and girls. A prostatic abscess is a very rare clinical variety of UTI, especially in neonates. We present the case of a 15-day-old male neonate who developed a rare variety of urosepsis. The baby was evaluated and found to have a prostatic abscess. Ultrasound of the abdomen showed an enlarged prostate gland with diffuse heterogeneous hypoechogenicity. Magnetic resonance imaging (MRI) of the pelvis showed an enlarged, lobulated prostate with T2 hyperintense signal and T1 hypointense signal and diffusion restriction. The post-contrast images in the pelvis-MRI also showed peripheral rim enhancement suggestive of a prostatic abscess. Urine culture showed growth of methicillin-resistant Staphylococcus aureus (MRSA). The baby was treated with intravenous vancomycin, and pus was drained through a transurethral approach. Phimosis can cause purulence in the prostate. Prostatic abscess usually has a good prognosis in neonates when diagnosed early and appropriate treatment was instituted.